Arabisk fængselslitteratur og den syriske digter Muhammad al-Maghut - Holmberg, Bo (Passage - Tidsskrift for litteratur og kritik, 2009)
Bo Holmberg: “Arabic Prison Literature and the Syrian Poet Muhammad al-Maghut” This article deals with some aspects of prison literature from the Middle East and mainly in Arabic. Prison literature may be literature written by prisoners either during imprisonment, or after imprisonment. It may also include literature by nonprisoners who are writing in a society where imprisonment is a constant threat for political, religious and moral reasons. Special attention is given to the situation in modern Syria, and the poetry of Muhammad al-Maghut (1934-2006) is high-lighted.